Implementasi Metode Tahfidz Qur’an di Yayasan Pendidikan Semesta Mengaji - Hidayati, Yusranida; Lubis, Sakban (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Memorizing the Al-Quran requires an appropriate method that is appropriate to the development of each child who memorizes it. The method used makes a major contribution to the formation of a golden generation of Islam who memorize and understand the Al-Quran in depth. The aim of this research is to determine the tahfiz Quran method implemented at the Semesta Education Foundation in terms of planning, implementation, evaluation and the obstacles faced. The method used in this research is qualitative with data collection techniques using participant observation and in-depth interviews. All existing data is analyzed using the stages of data condensation, data display and verification. The findings in this research are that the planning of the tahfidz method for memorizing the Koran at the Semesta Mengaji Education Foundation is carried out at the beginning of each school year. However, if there is an urgent problem that arises related to the implementation of the tahfidz method in memorizing the Koran, a solution will be discussed and a solution will be sought at daily meetings, up to monthly meetings. The implementation of the Quran tahfidz method at the Semesta Mengaji Education Foundation uses the tikrar method, where a student repeats the verses approximately 5 to 40 times until they are memorized. Evaluation of the tahfidz method for memorizing the Koran at the Semesta Mengaji Education Foundation is carried out with the Final Evaluation of Students, where students take a level test, written test and unwritten test. Obstacles faced in memorizing the Koran at the Semesta Mengaji Education Foundation include immature age levels, variations in comprehension ability in memorizing, motivation to memorize that is not consistent and is not fluent in reading the Al-Quran.